Test-retest reliability of a functional electromechanical dynamometer on swing eccentric hamstring exercise measures in soccer players - Antonio Jesús Sánchez-Sánchez; Luis Javier Chirosa-Ríos; Ignacio Jesús Chirosa-Ríos; Agustín José García-Vega; Daniel Jerez-Mayorga (PeerJ, 2021)
Background The use of a functional electromechanical dynamometer (FEMD) has been proposed as a valid and effective tool to evaluate specific movement patterns. The aim of this study was to determine the reliability of FEMD on swing eccentric hamstring exercise (SEHE) measures in soccer players. Methods Nineteen federated male soccer players (20.74 ± 4.04 years) performed the SEHE at three different isokinetic velocities (20–40–60 cm/s). These evaluations were conducted in four sessions, two for familiarization and two for registration. The average and maximum load (N) of the three isokinetic velocities was calculated from the values obtained from the FEMD (Dynasystem®, Bangalore). Results The main results of this research showed that the reliability was high for the average load in the condition of 40 cm/s, presenting the highest ICC value (0.94). For maximum load, reliability was high in the condition of 20 cm/s. The manifestation of the most reliable load was the maximum load (ICC = 0.91–0.87). Conclusions FEMD (Dynasystem®, Bangalore) is a reliable device to evaluate the eccentric strength of the hamstring muscles in soccer players.